Role of broadcast media in the dissemination of agricultural knowledge. - Nazri, Mohammad Reza; Hassan, Md. Salleh; Parhizkar, Saadat; Hassanpour, Behrooz; Yasin, Megat Al-Imran (Societe de Physique et d'Histoire Naturelle de Geneve, 2012)
The aim of this study was to assess the role and effectiveness of electronic media (TV and Radio) in the dissemination of agricultural information to the farmers. Three hundred twenty two farmers from Fars and Kohgiluyeh va Buyer Ahmad provinces participated in the study which involved a pre test, an intervention, and a post test experience. The farmers were randomly assigned to an educational program through television or radio. The interventions were similar in contents and time of presentation and varied only in the type of media. Data was collected using a structured questionnaire before and after intervention. The results showed that knowledge of farmers was not adequate and the mean score of their knowledge in Fars and Kohgiluyeh va Buyer Ahmad provinces were 3.99 ±1.94 and 3.73 ± 2.11 respectively which after exposure to educational programs through radio and television increased to 6.41 ± 1.50 and 6.26 ± 1.67 respectively. A significant and positive correlation was observed between farmers’ knowledge and their educational level. Mass media offer effective channels for communicating agricultural messages, which can increase level of knowledge and influence behavior of the audiences Broadcast media, remain a vital part of development and farming systems; agricultural education intervention programmes will be more fruitful if they are conveyed through the radio and television. Such programmes should result in heightened farmer awareness and consequently improvement of their practice for purpose of development in agricultural sector.